2008
DOI: 10.1002/bsl.822
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the CJDATS Co‐Occurring Disorders Screening Instruments (CODSIs) among Minority Offenders

Abstract: Previous research has shown the performance of the CJDATS Co-Occurring Disorders Screening Instruments (CODSI-MD and SMD)--six- and three-item instruments to screen for any mental disorder (CODSI-MD) and for severe mental disorders (CODSI-SMD), respectively--to be comparable or superior to other, longer instruments. This study tested the stability of the performance of the CODSI-MD and SMD across three racial/ethnic groups of offenders entering prison substance abuse treatment programs (n = 353), consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Like that by Duncan et al (2008), the current study found an association between antisocial personality disorder and in-prison violence. Antisocial personality disorder is likely a risk for predatory aggression, defined as violent acts that are ''planned, purposeful and goal directed'' (Scott & Resnick, 2006).…”
Section: Discussionmentioning
confidence: 40%
“…Like that by Duncan et al (2008), the current study found an association between antisocial personality disorder and in-prison violence. Antisocial personality disorder is likely a risk for predatory aggression, defined as violent acts that are ''planned, purposeful and goal directed'' (Scott & Resnick, 2006).…”
Section: Discussionmentioning
confidence: 40%
“…For one study we calculated these values by sex from raw data provided [ 26 ]. For another study [ 33 ], data were weighted by sex, as sampling was stratified. Since no other studies accounted for over-sampling by sex, we re-calculated un-weighted statistics from the raw data provided.…”
Section: Methodsmentioning
confidence: 99%
“…Three of the medium quality studies could not find any ethnic variations in prevalence rates of psychotic disorders (Duncan et al, 2008;Simpson et al, 2003;Teplin, 1990). One of these three studies (Teplin, 1990) was not hypothesis driven when comparing ethnicity.…”
Section: Medium Quality Studiesmentioning
confidence: 95%
“…A total of eleven studies received a medium score on methodological quality (Butler et al, 2007;Duncan et al, 2008;Hoffmann, 2006;Karnik et al, 2010;Linhorst et al, 1998;Paradis et al, 1999;Perry et al, 2013;Simpson et al, 2003;Teplin, 1990;Vinkers et al, 2011;Vinkers, de Beurs, et al, 2010).…”
Section: Medium Quality Studiesmentioning
confidence: 99%